2013
DOI: 10.1007/jhep08(2013)033
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of dimension-six operators relevant for the Higgs decays h → γγ, γZ

Abstract: The discovery of the Higgs boson has opened a new window to test the SM through the measurements of its couplings. Of particular interest is the measured Higgs coupling to photons which arises in the SM at the one-loop level, and can then be significantly affected by new physics. We calculate the one-loop renormalization of the dimensionsix operators relevant for h → γγ, γZ, which can be potentially important since it could, in principle, give log-enhanced contributions from operator mixing. We find however th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
182
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(187 citation statements)
references
References 16 publications
(70 reference statements)
5
182
0
Order By: Relevance
“…These are related to the coefficients at the new physics scale through RGE equations [110][111][112][113][114][115][116][117].…”
Section: Jhep03(2015)157mentioning
confidence: 99%
“…These are related to the coefficients at the new physics scale through RGE equations [110][111][112][113][114][115][116][117].…”
Section: Jhep03(2015)157mentioning
confidence: 99%
“…In refs. [77,78] an effective approach was used in which only the SM fields are retained and all the composite resonances are integrated out. In this framework it was shown that two effective operators…”
Section: Jhep10(2013)160mentioning
confidence: 99%
“…[77,78], in our approach the resonances are included in the effective theory and the effective operators O Hq and O Hq are not present directly in our Lagrangian. At low energy, however, they are generated through the exchange of resonances of mass m with a coefficient y 2 /m 2 .…”
Section: Jhep10(2013)160mentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the coefficients constrained in our fit correspond to those defined at the electroweak scale, c i ≡ c i (v), which can be related to c i (Λ) at the matching scale by RGE running [45][46][47][48][49][50][51][52]. We neglect dimension-8 operators in our analysis, as well as four-fermion operators (other thanc (3)l LL that modifies the input parameter G F ), whose effects on Z-pole measurements are formally of the same order as dimension-8 operators due to the lack of linear interference terms with the SM amplitudes [16].…”
Section: Jhep03(2016)089mentioning
confidence: 88%